2016
DOI: 10.1212/wnl.0000000000002679
|View full text |Cite
|
Sign up to set email alerts
|

Preinjury somatization symptoms contribute to clinical recovery after sport-related concussion

Abstract: Preinjury somatization symptoms contribute to reported postconcussive symptom recovery via their influence on acute postconcussive symptoms. The findings highlight the relevance of premorbid psychological factors in postconcussive recovery, even in a healthy athlete sample relatively free of psychopathology or medical comorbidities. Future research should elucidate the neurobiopsychosocial mechanisms that explain the role of this individual difference variable in outcome following concussive injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 37 publications
7
98
0
8
Order By: Relevance
“…With this in mind, it is interesting that the general factor also correlated robustly with several pre-injury clinical variables, including pre-injury baseline somatic and distress symptoms. This finding is consistent with a wealth of evidence indicating a direct link between pre-injury emotional functioning and response to concussion which in turn points to the need for more investigation into the mechanisms by which pre-injury risk and resilience factors influence patients’ responses to injury and courses of recovery (Broshek, De Marco, & Freeman, 2015; Nelson, Tarima, et al, 2016; Root et al, 2016). …”
Section: Discussionsupporting
confidence: 86%
“…With this in mind, it is interesting that the general factor also correlated robustly with several pre-injury clinical variables, including pre-injury baseline somatic and distress symptoms. This finding is consistent with a wealth of evidence indicating a direct link between pre-injury emotional functioning and response to concussion which in turn points to the need for more investigation into the mechanisms by which pre-injury risk and resilience factors influence patients’ responses to injury and courses of recovery (Broshek, De Marco, & Freeman, 2015; Nelson, Tarima, et al, 2016; Root et al, 2016). …”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, these findings do not rule out the possibility that acute neuropsychological data could be informative for prognostic purposes in mTBI or other patient populations (Dischinger, Ryb, Kufera, & Auman, 2009; McCrea et al, 2013; Meehan, Mannix, Monuteaux, Stein, & Bachur, 2014; Nelson, Tarima, et al, 2016). At the present time, however, the findings suggest that clinicians can continue to apply standard clinical criteria to assess patients for mTBI; neurocognitive assessment may provide supporting data on patients’ presenting concerns but is not useful for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 81%
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
“…Five studies by Iverson63 and Lau and colleagues (refs. 4, 66, 64 and 87) used the same cohort of football players and thus findings relating to specific predictors in boxes 1-3 are represented by only one of these five studies.
Injury severity characteristics associated with recovery Loss of consciousness: Yes: Chermann81; Pellman122; Guskiewicz110; Asplund89; McCrea91; Miller56; Benson115; Heyer80; Zemek57 No: Brown118; Guskiewicz123; Hinton-Bayre124; Nelson21; Bock49; Corwin48; Zuckerman102; Terwilliger83; Morgan58; Erlanger119; Lau4; McCrea25; Ellis95; Makdissi120; McDevitt88; Nelson78; Merritt5; Meehan6; Gibson96; Chrisman75; Collins 125; Meehan90 Post-traumatic amnesia/‘amnesia’: Yes: Benson115; Chrisman75 (males only); Guskiewicz110; Heyer80; McCrea91; Lovell126; Collins125; Meehan6; Zuckerman102 No: Brown118; Guskiewicz123; Hinton-Bayre124; Nelson21; Asplund89; Bock49; Terwilliger83; Meehan90; Lau66; McCrea25; Ellis95; Makdissi120; Nelson (2016)78; Merritt5; Eisenberg68; Gibson96 Retrograde amnesia: Yes: Asplund89; McCrea91; Zuckerman102; Nelson78; Pellman122 No: Lau66; Merritt5; Heyer80; Collins125; Nelson78; Delayed removal from play/or additional head trauma: Yes: Asken117; Terwilliger83; Heyer80 No: NoneNote: First author and reference citation.
…”
Section: Resultsmentioning
confidence: 99%